(untitled) (Journal of Applied Membrane Science & Technology, 2025)
Biogas is a renewable energy source mainly made up of methane (CH4) and carbon dioxide (CO2), demands excellent CO2 separation with the goal to reach the minimum of 95% purity for CH4 needed to produce biomethane. Pressure swing adsorption (PSA) and chemical absorption are the example of conventional techniques to remove CO2 that have been commonly used, despite their limitations related to high energy consumption, operational complexity and efficiency. These limitations highlight the need for innovative and sustainable approaches to improve purification of biogas. This study explores the potential of using fillers based on polyphenylene sulfide (PPS) in polymeric membranes as a novel approach to enhance CO2 separation from biogas. PPS makes a great option for membrane applications due to its aromatic polymer that is popularly known for its chemical resistance and thermal stability. Current developments, such as porous carbon-derived materials (PCs) and nitrogen-sulfur co-doped porous carbon (NSPCs), exhibit intriguing features for improving gas separation through their interactions with CO2. The incorporation of PPS-based fillers into polysulfone (PSf) membranes is anticipated to further enhance CO2 separation performance. This analysis highlighted significant advancements in membrane technology by comparing PPS-based systems with conventional techniques to demonstrate their benefits especially in terms of energy efficiency and simplified procedures. In addition, the review highlighted the current recent circumstances associated with material compatibility and scalability, which suggests future research areas. Development in this sector offers potential processes to completely transform the utilization of biogas by providing sustainable and efficient techniques for CO2 separation, which would enhance the production of biomethane.